MODEL SISTEM PENGATURAN LALU LINTAS SECARA NIRKABEL PADA PINTU PERLINTASAN KERETA API - Haryadi, Hartono; Hugeng, Hugeng; Riyansyah, Deris (Universitas Tarumanagara, 2007)
When the train will pass by quickly and if there are any vehicle trapped between trajectory doors, the custodian post contact the train use the communications radio. It can cause fatal if the custodian do mistake. The traffic arrangement system at train trajectory door has been design to change role of the custodian post, so that mount accident at train trajectory door is more and more lessened